Enhanced visible light photocatalytic activity of CeO2@Zn0.5Cd0.5S by facile Ce(IV)/Ce(III) cycle - Zain Ul Abideen; Fei Teng; Wenhao Gu; Zhicheng Yang; An Zhang; Fangdi Zhao; Abid Hussain Shah (Arabian Journal of Chemistry, 2020)
In this study, CeO2@Zn0.5Cd0.5S heterostructure (Ce@ZCS) is synthesized via a simple two-step hydrothermal method. The effect of CeO2 loading on the visible-light photoactivity of Zn0.5Cd0.5S is mainly investigated. It is found that Ce@ZCS shows a 1.9 times activity as high as ZCS for the MB degradation. The improved activity mainly results from the significant enhanced charge separation by CeO2, in which the electron transfer is obviously promoted by the facile Ce(IV)/Ce(III) cycle. The excited electrons of ZCS is easy to transfer to CeO2, thus obviously increasing the charge separation of ZCS. The accepted electrons by CeO2 may easily be captured by the adsorbed O2 to form O2·−, and then O2·− could combine with H+/H2O to form HO2·, and ·OH. Finally, O2·−, h+ and ·OH are confirmed as the major oxidative species in photocatalytic reaction for Ce@ZCS, and a possible photocatalytic mechanism is proposed. The cheap, efficient Ce@ZCS photocatalyst could be applied for practical waste water treatment. Keywords: Ce(IV)/Ce(III) cycle, CeO2@Zn0.5Cd0.5S, Electron transfer, Photocatalysis